Implant placement post extraction in esthetic single tooth sites: when immediate, when early, when late?. Issue 1 (February 2017) - Buser, Daniel; Chappuis, Vivianne; Belser, Urs C.; Chen, Stephen
Abstract: Implant placement in post‐extraction sites of single teeth in the esthetic zone has been a topic of great interest in the field of implant dentistry since 1990. Triggered by the development of guided bone regeneration, the concept of immediate implant placement became quite popular in the 1990s. In the past 12 years, however, the dental community has begun to focus increasingly on the esthetic outcomes of post‐extraction implant placement and several studies indicated a significant risk for the development of mucosal recessions with immediate implants. Parallel with this, significant progress has been made in the understanding of tissue biology in terms of hard and soft tissue alterations post extraction, based on preclinical, clinical and radiological studies. This knowledge has helped better to understand the etiology of these esthetic complications with immediate implant placement. The present review first analyzes the various phases of the development of therapeutic strategies over the years for post‐extraction implant placement in single tooth sites in the esthetic zone. It presents the current knowledge concerning the terminology with immediate, early and late implant placement, the risk factors for the development of esthetic complications, and the selection criteria for the various treatment options. In the second part, clinical recommendations are given, since a clinician active in this field of implant therapy can use all treatment options depending on the preoperative analysis including a 3D cone beam computed tomography. The selection criteria for all four treatment options are presented and documented with typical case reports to illustrate the current treatment approaches applied in daily practice.